Internal Use of Ajan Vruksha/ Khandu Chakka (Ehretia Laevis Roxb). Plant Leaves Powder in Shoulder Pain Management. – Case Report - Rushikesh Thakre; Abhyuday Meghe; Ketaki Thakre; Pradip Tekade (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction— Shoulder pain and stiffness are common features among working women. It is affectingtheir day to day life style.The main symptoms of the patient and the important clinical findings:- Patient was suffering fromsevere pain in right shoulder with restricted movement of right shoulder from 8 days. Patient was assessedby ( SPADI) Shoulder Pain & Disability Index.The main diagnoses, therapeutics interventions, and outcomes:- Ehretia Laevis Roxb. leaves powdercapsules was made up of 250 mg. Patient was advised to take two capsules in morning and two capsules atnight after food. Daily 1 gm powder was administered internally for 7 daysOn the day zero pain score was 80%, on third day of treatment pain score was 54% and on seventh day painscore was 0. On the day zero disability score was 95%, on third day disability score was 55% and on seventhday score was 0.Conclusion—. Patient cured from pain and shoulder disability by internal use of Ehretia Laevis Roxb.leaves powder within seven days